Proceedings of the 17th Annual International Conference on Mobile Computing and Networking 2011
DOI: 10.1145/2030613.2030625
|View full text |Cite
|
Sign up to set email alerts
|

Detecting driver phone use leveraging car speakers

Abstract: This work addresses the fundamental problem of distinguishing between a driver and passenger using a mobile phone, which is the critical input to enable numerous safety and interface enhancements. Our detection system leverages the existing car stereo infrastructure, in particular, the speakers and Bluetooth network. Our acoustic approach has the phone send a series of customized high frequency beeps via the car stereo. The beeps are spaced in time across the left, right, and if available, front and rear speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(95 citation statements)
references
References 24 publications
0
91
0
4
Order By: Relevance
“…Each neighboring peer has a unique physical location for restraining the location uncertainty of a smartphone. Second, a number of research work [19,26] has shown that highly accurate relative ranging can be achieved within a car (passenger vs. driver side) or between a pair of mobile devices (at centimeter accuracy) by using sound signals.…”
Section: Peer Assisted Localizationmentioning
confidence: 99%
“…Each neighboring peer has a unique physical location for restraining the location uncertainty of a smartphone. Second, a number of research work [19,26] has shown that highly accurate relative ranging can be achieved within a car (passenger vs. driver side) or between a pair of mobile devices (at centimeter accuracy) by using sound signals.…”
Section: Peer Assisted Localizationmentioning
confidence: 99%
“…Yang et.al. [36,37] introduce an acoustic relative-ranging system that classifies on which car seat a phone is being used leveraging the car's audio infrastructure. This approach relies on the vehicle's audio system.…”
Section: Related Workmentioning
confidence: 99%
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. phone for incoming text messages while in driving mode as discussed in [26,36].…”
Section: Introductionmentioning
confidence: 99%
“…Location information is essential for a wide range of pervasive and mobile applications, such as wireless sensor networks, mobile social networks, location-based services, smart space, [1], [2], [3] etc. Especially, in the literature of indoor localization, a well-known research direction in pervasive and mobile computing, many techniques have been proposed in the past two decades.…”
Section: Related Workmentioning
confidence: 99%
“…In most of today's applications such as pervasive medicare, smart space, wireless sensor surveillance, mobile peer-to-peer computing, [1], [2], [3] etc., location is one of the most essential contexts. In the literature of pervasive computing, wireless indoor localization has been extensively studied and many solutions are proposed to provide room-level localization services, such as locating a person or a printer in an office building.…”
Section: Introductionmentioning
confidence: 99%